Climate change - induced hazards on touristic island beaches: Cyprus, Eastern Mediterranean - Monioudi, Isavela N.; Velegrakis, Adonis F.; Chatzistratis, Dimitris; Vousdoukas, Michalis I.; Savva, Christos; Wang, Dandan; Bove, Gerald; Mentaschi, Lorenzo; Paprotny, Dominik; Morales-Nápoles, Oswaldo; Chatzipavlis, Antonis E.; Hasiotis, Thomas; et al. (Frontiers in Marine Science, 2023)
This contribution presents an assessment at a regional (island) scale of the beach erosion due to storm events under Climate Change. The approach adopted to assess beach erosion at the island scale consisted of three modules. First, the location, dimensions and other attributes of the Cypriot beaches were recorded on the basis of widely-available satellite imagery. Secondly, sea levels and waves were modeled along the coast under different climatic scenarios and dates in the 21st century. Finally, using these projections beach retreat due to the relative mean sea level rise (RSLR) and extreme sea levels (ESLs) was estimated using ensembles of analytical and numerical cross-shore morphodynamic models, respectively. Extreme sea levels (ESLs) were projected to (a) increase by up to 60 % in 2100 from their baseline (2000) levels, and (b) vary along the coast, with the highest ESLs (and corresponding waves) projected for the southern and western coasts. The mostly narrow Cypriot beaches (91 % recorded maximum widths of < 50 m) showed increased exposure to erosion. In 2100, about 47 % and 72 % (based on the median model estimates) of the 241 unprotected Cypriot beaches will be permanently eroded, due to mean sea level rise (SLR), to 50 % of their present maximum width, depending on the scenario. In addition to the long-term erosion due to SLR, severe storm erosion is projected by 2050 even under the RCP4.5 scenario; the 100-year extreme sea level event (ESL100) may overwhelm (at least temporarily) 49 % of the currently unprotected Cypriot beaches without effective adaptation responses, with the most exposed beaches located along the northern coast. As the beach carrying capacity and hedonic value will be severely compromised, effective adaptation policies and technical measures will be urgently required.